2019
DOI: 10.5194/hess-23-4419-2019
|View full text |Cite
|
Sign up to set email alerts
|

Detection and attribution of flood trends in Mediterranean basins

Abstract: Abstract. Floods have strong impacts in the Mediterranean region and there are concerns about a possible increase in their intensity due to climate change. In this study, a large database of 171 basins located in southern France with daily discharge data with a median record length of 45 years is considered to analyze flood trends and their drivers. In addition to discharge data, outputs of precipitation, temperature, evapotranspiration from the SAFRAN reanalysis and soil moisture computed with the ISBA land s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 76 publications
5
37
0
3
Order By: Relevance
“…This is attributable to other factors which modulate flood response, such as initial soil moisture. For example, Tramblay et al (2019) found that, despite the increase in extreme precipitation, the fewer detected annual occurrences of extreme floods in 171 Mediterranean basins were likely caused by decreasing soil moisture. The relationship between the flow rate and the initial saturation state of the soil is often non-linear, and the effect of antecedent soil moisture strongly depends on soil type and geology.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributable to other factors which modulate flood response, such as initial soil moisture. For example, Tramblay et al (2019) found that, despite the increase in extreme precipitation, the fewer detected annual occurrences of extreme floods in 171 Mediterranean basins were likely caused by decreasing soil moisture. The relationship between the flow rate and the initial saturation state of the soil is often non-linear, and the effect of antecedent soil moisture strongly depends on soil type and geology.…”
Section: Introductionmentioning
confidence: 99%
“…The water contained in the unsaturated, or vadose zone, is an important driver for floods with soils close to saturation having more probability to produce runoff when subjected to precipitation inputs (Zehe et al, 2005;Ivancic and Shaw, 2015;Woldemeskel and Sharma, 2016;Bennett et al, 2018;Wasko and Nathan, 2019). This is particularly true in the Mediterranean context where several studies have shown the strong influence of soil moisture on flood generation processes (Brocca et al, 2008;Penna et al, 2011;Tramblay et al, 2010Tramblay et al, , 2019Uber et al, 2018). Similarly, Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…There is a climatic trend towards a drying of the Mediterranean region, both during the historical period but also in future climate scenarios, showing a decrease in precipitation amounts and occurrence, associated with an increasing frequency of drought episodes (Hoerling et al, 2012;Polade et al, 2014Polade et al, , 2017Hertig and Tramblay, 2017;Lionello and Scarascia, 2018;Tramblay et al, 2020). For a RCP8.5 emission scenario, Giannakopoulos et al (2009) and Polade et al (2014) both estimate a mean decrease up to −30 % of the annual precipitation in the Mediterranean region by the end of the century and an increase of dry days ranging between +1 to +3 weeks per year.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, initial soil moisture conditions prior to flood events play a key role in causing floods. An increase in rainfall intensity does not necessarily result in an increased flood risk because the runoff coefficient can be very variable over time and space due to complex interactions between precipitation and infiltration processes (Tramblay et al, 2019). The type of soil can also have different sensitivity to changing climatic conditions (Camici et al, 2017;Piras et al, 2016).…”
Section: Introductionmentioning
confidence: 99%